Mannitol Reduces Spinal Cord Edema in Rats with Acute Traumatic Spinal Cord Injury - Zhang, Chao; Hu, Anming; Jing, Yingli; Yang, Degang; Li, Jianjun (Letters in Drug Design & Discovery, 2020)
Background: The research about anti-edema effects of mannitol on acute traumatic spinal cord injury (SCI) in rats is rare. Objective: This study aimed to explore the effect of mannitol on spinal cord edema after SCI in rats. Methods: Seventy-eight adult female rats were assigned to three groups randomly: a sham control group (n = 18), a contusion and normal saline contrast group (n=30), and a contusion and mannitol treatment group (n=30). We used the open-field test to estimate the functional recovery of rats weekly. Spinal cord water content was measured to determine the spinal cord edema. The ultrastructure features of the injured dorsolateral spinal cord were determined on the 7th day after SCI by HE staining. Results: The mannitol group had greatly improved Basso-Beattie-Bresnahan (BBB) scores when compared with the saline contrast group. The spinal cord water content was increased significantly after SCI, and there was no significant difference in the water content between the NaCl and mannitol groups 1 day after SCI. The water content at 3 and 7 days after SCI was significantly lower in the mannitol group than in the NaCl group (p < 0.05). Mannitol can reduce spinal cord edema by increasing the number of red blood cells in the injured spinal cord and decrease the ratio (dorsoventral diameter/ mediolateral diameter) of spinal cord 7 days post-SCI. Conclusion: Mannitol increases recovery of motor function in rats, reduces spinal cord edema and increases the number of red blood cells in the injured spinal cord, decreasing the ratio of spinal cord to reduce pressure.
Keywords: rats